Implementasi In-House Training (IHT) Sebagai Strategi Akselerasi Literasi Teknologi Pendidik di SMA Negeri 6 Karawang - Faddal, Afaf Fatina; Permana, Hinggil; Az Zahro, Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of In-House Training (IHT) as a principal's strategy in accelerating educators' technological literacy at SMA Negeri 6 Karawang. This research is motivated by the importance of improving teachers' technological literacy in facing the digital transformation of education and the need for principals' strategies in supporting the development of educators' competencies so that learning becomes more effective, innovative, and adaptive to technological developments. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation with key informants: the principal, teachers, and the school's ICT team. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of IHT was carried out systematically and directed according to the principal's strategy in improving educators' technological literacy. Implementation began with an analysis of training needs based on teachers' actual conditions, especially regarding their ability to use technology in the learning process. The implementation of IHT was carried out through workshops and practices that focused on the use of learning technologies such as Google Forms, Kahoot, Gamma, Learning Management Systems, and the use of Artificial Intelligence. Teachers were given the opportunity to directly practice using these applications to make them easier to apply in daily learning activities. The implementation of IHT has been proven to improve educators' technological literacy skills, strengthen digital culture in schools, and encourage more interactive and effective learning. And That’s, IHT is an effective strategy for improving the quality of learning in the digital age.